HUBUNGAN ANTARA FAKTOR IBU DENGAN STATUS GIZI BALITA DI PUSKESMAS HINAI KIRI KECAMATAN SECANGGANG KABUPATEN LANGKAT TAHUN 2020: Correlation Between Mother Factor And Nutrition Status Of Toddlers In Hinai Kiri Public Health Center (Puskesmas Hinai Kiri) Secanggang Langkat District 2020 - Yerni, Arnof; Sihombing, Setia (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2021)
Abstract Toddlers is the age group that is most vulnerable to nutritional deficiencies and is considered a nutritional vulnerable group. This research was done using a correlative association approach, beinga survey research concerning the correlation between research variables and confirming the proposed hypothesis. The population of this research was all outpatient mothers with toddlersin the polyclinic of Puskesmas Hinai Kiri (Hinai Kiri Public Health Center) Kecamatan Secanggang Kabupaten Langkat numbering 54 people, with accidental sampling technique. From the univariate analysis result was found that 33 mothers (61,1%) have high knowledge,29 mothers (53,7%) were from the old age group, 33 mothers have high education (61,1%) and 32 mothers (59,3%) being unemployed with 28 mothers (51,9%) have high number of children, 28 mothers (51,9%) from a low family income group, and 38 mothers (70,4%) have good toddler nutrition status. From the bivariate analysis result using chi squaretest (CI 95% and a= 0,05) was found that the correlation between knowledge and toddler nutrition statsus is (p- value = 0,009), the correlation between age and toddler nutrition status is (p-value = 0.039), the correlation between education and toddler nutrition status is (p-value = 0,003), the correlation between occupation and toddler nutrition status is (p-value= 0,045), the correlation between income and toddler nutrition status is ( P –Value = 0,002), and the correlation between number of childern and toddler nutrition status is (P-Value= 0,003).   Keyword(s) : Toddler nutrition